2017
DOI: 10.1111/bph.13950
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin receptors: molecular pharmacology and signalling in the context of system bias

Abstract: Melatonin, N-acetyl-5-methoxytryptamine, an evolutionally old molecule, is produced by the pineal gland in vertebrates, and it binds with high affinity to melatonin receptors, which are members of the GPCR family. Among the multiple effects attributed to melatonin, we will focus here on those that are dependent on the activation of the two mammalian MT and MT melatonin receptors. We briefly summarize the latest developments on synthetic melatonin receptor ligands, including multi-target-directed ligands, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
161
0
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(188 citation statements)
references
References 188 publications
1
161
0
9
Order By: Relevance
“…Both receptors are G-coupled 7-transmembrane receptors [33]. For a more detailed description of melatonin receptor signaling pathways, the reader is referred to other expert reviewers [34, 35]. In short, both receptors are tightly coupled to the Gi/cAMP pathway.…”
Section: Role Of Melatonin Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both receptors are G-coupled 7-transmembrane receptors [33]. For a more detailed description of melatonin receptor signaling pathways, the reader is referred to other expert reviewers [34, 35]. In short, both receptors are tightly coupled to the Gi/cAMP pathway.…”
Section: Role Of Melatonin Receptorsmentioning
confidence: 99%
“…Cecon et al [34] prepared lists of human tissues in which melatonin receptors have been identified. Thus melatonin, via MT 1 and MT 2 receptors, regulates a variety of physiological and neuroendocrine functions.…”
Section: Role Of Melatonin Receptorsmentioning
confidence: 99%
“…Many of melatonin's biological effects are mediated by the activation of melatonin receptors . The effects of melatonin are mediated by two receptors, which are expressed in a function‐specific fashion . The melatonin receptors of β cells positively regulate cellular functions and affect insulin secretion in the subtype‐dependent mode .…”
Section: Discussionmentioning
confidence: 99%
“…In their review, Cecon et al (2018) make a gentle start by explaining that MT 1 and MT 2 receptors are both GPCRs, with several coupling targets, before going on to outline their distribution, structure, function and pharmacology. The authors then discuss the possibility of developing multi-target-directed, 'hybrid ligands', which combine melatonin with other drugs, to achieve additive therapeutic effects.…”
mentioning
confidence: 99%
“…Environmental differences include cell type; cell context-dependent receptor expression; receptor homo and heterodimerization; and even features of the lipid membrane. These variables also influence epigenetic responses to melatonin, and Cecon et al (2018) suggest that this could explain why the effects of melatonin on circadian clock gene expression depend on cell type. However, the coup de grace is the evidence that over 300 different proteins interact with the MT 1 receptor and only about 50 of them overlap with proteins that interact with the MT 2 receptor.…”
mentioning
confidence: 99%